Analisis Pengendalian Persediaan Bahan Baku dengan Metode EOQ : Studi Kasus pada Bahan Baku Masakan Ikan Mas di Warung Nasi Ibu Nani - Sri Ayu Agustini; Barin Barlian; Depy Muhamad Pauzy (CV. Ulil Albab Corp, 2022)
This study was to determine the planning of raw material inventory, the maximum inventory of raw materials and the total cost of raw material inventory at Warung Nasi Ibu Nani. The raw material used at Warung Nasi Ibu Nani is carp, which is processed into pepes, pesmol, sweet areaca nut, grilled and fried. This study uses interview data collection techniques, observation, library research and recording, research. The method used in this research is comparative. The data analysis method used is Economic Order Quantity (EOQ), Safety Stock, Reorder Point, Maximum Inventory and Total Inventory Cost. Based on the result of the analysis, it was found that the supply of raw materials at Warung Nasi Ibu Nani using EOQ and without using EOQ there was a difference for period 1 89,74%, period 2 89,74%, period 3 89,74%, period 4 89,74%, period 5 89,74%, period 6 89,74%, period 7 89,74%, period 8 89,74%, period 9 89,74%, period 10 192,12%, period 11 131,17%, period 12 89,74%, period 13 89,74%, period 14 89,74% dan period 15 89,74%.